Assessment of natural radioactivity in various commercial tiles used for building purposes in Nigeria - Joel, E.S.; Maxwell, O.; Adewoyin, O.O.; Ehi-Eromosele, C.O; Embong, Z.; Oyawoye, F. (ScienceDirect, 2018)
In this study, we evaluated the activity concentration of natural radionuclides (226Ra, 232Th and 40K) for fifteen (15) different brands of tile samples used for building purposes in Nigeria. The tile samples were analyzed using High purity Germanium gamma detector. The mean activity concentrations of 226Ra, 232Th, and 40K were observed to be 61.1 5.5 Bq/kg, 70.2 6.08 Bq/kg and 514.7 59.8 Bq/kg respectively. Various hazard indices such as absorbed dose rate, external and internal hazard index, annual effective dose rate, Gamma activity Index (Ig) and Alpha Index (Ia) were calculated. The obtained results showed that the mean radium equivalent activity (Raeq), the absorbed dose rate (D), external and internal hazard index, the annual effective dose (AEDR) equivalent, Gamma activity Index (Ig) and Alpha Index (Ia) were: 204.42 Bq/kg, 177.61 nGyh1 , 0.55, 0.77, 0.96 mSvyr1 , 0.74 and 0.32 respectively. The average value of radium equivalent obtained in this study is less than that of the recommended value of 370 Bq/kg but the average values of the other radiological hazards for some samples are found to be slightly above international recommended values except Hex, Hin and AEDE which are within the international reference value of unity. The measured concentrations of these radioactive materials were correlated with other previous result obtained from similar tile materials used in other countries and found to be in good agreement with the international standard, however, the tiles are recommended for decoration purposes in Nigeria.